2005
DOI: 10.1016/j.femsle.2005.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of over-expression of phasin gene fromAeromonas hydrophilaon biosynthesis of copolyesters of 3-hydroxybutyrate and 3-hydroxyhexanoate

Abstract: The gene phaPAh, encoding the protein phasin that is associated with poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) granule of Aeromonas hydrophila 4AK4, was cloned and characterized. Recombinant strains harboring additional copies of the phasin gene (phaPAh) and the polyhydroxyalkanoate (PHA) synthase gene (phaCAh) accumulated PHBHHx copolyesters consisting of 21 mol% 3-hydroxyhexanoate (3HHx) as compared to 14 mol% 3HHx produced by wild type strain. The molecular weight of PHBHHx produced by the abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
0
28
0
2
Order By: Relevance
“…Previous studies have indicated that PhaPs have an enhancing effect on PHA biosynthesis in vivo (9,10,24,25). To further investigate this effect, we performed in vitro polymerization activity assays in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that PhaPs have an enhancing effect on PHA biosynthesis in vivo (9,10,24,25). To further investigate this effect, we performed in vitro polymerization activity assays in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These observations include PhaP Ac expression leading to enhanced accumulation of PHA and/or altering the copolymer composition, likely by influencing the activity and substrate specificity of PhaC Ac (8,9). The same phenomenon was observed in recombinant bacteria between the PhaC and PhaP derived from Aeromonas hydrophila (10). However, these in vivo studies have not focused on the role of PhaP at the molecular level.…”
mentioning
confidence: 83%
“…Furthermore, this phasin binds to DNA nonspecifically through a histone-like domain and plays a key role in intracellular localization and equal distribution of PHA granules to daughter cells during cell division (19,44). Last, PhaP from A. hydrophila (PhaP Ah ) was also observed to act as a positive regulator of the gene that encodes the PHA synthase in this organism, as the overexpression of phaP increased the expression of phaC (45).…”
Section: Role Of Phasins In Pha Metabolismmentioning
confidence: 99%
“…The results of reverse transcription-polymerase chain reaction suggested that phasin PhaP Ah , regulated phaC Ah gene at the transcription level. [31] Recombinant Ralstonia eutrophaPHB-4 harboring mutated PHA synthase genes phaC Ac from Aeromona caviae produced a PHA copolymer PHBHHx with 3.5 mol-% of 3HHx from soybean oil. When the mutants of phaC Ac gene were applied to this production system, the 3HHx fraction in copolymers varied in the range of 0-5.1 mol-%.…”
Section: Isolation Of Pha Synthases With Low Substrate Specificity Frmentioning
confidence: 99%